The Textual Practices of Jan Jiří Harant of Polžice and Bezdružice Between Family Memory, Cultural Translation and Exile Everydayness - Prchal Pavlíčková, Radmila (Dějiny – teorie – kritika, 2020)
The study analyses textual practices of Jan Jiří Harant of Polžice and Bezdružice (1580–1649?). This knight and exile engaged in several textual and artistic activities. Between 1624–1648 he wrote his memoirs in Czech. In the 1630s, he translated into German the travel account of his older brother, Kryštof Harant, which described his journey to the Holy Land. For this book translation he also prepared his brother’s biography and numerous illustrations. In exile, he then wrote a number of genealogies and drew a genealogy for his son’s book of military memories. This study contextualizes all textual and artistic activities of Jan Jiří Harant which have been so far researched separately and have not received complex interdisciplinary attention. Here, they are analysed in the context of contemporary practices of textual production and reproduction, book culture and the processes of reading and writing. Building on this well documented example, the author shows specific ways in which an aristocratic family in exile used texts and images in order to substitute for other ways of commemoration. Aside from entertainment, these practices also helped preserve and cultivate family memory, served its selfpresentation, and facilitated its integration in a foreign environment.